2006
DOI: 10.1093/sleep/29.12.1543
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Among Japanese Adolescents: A Nationwide Representative Survey

Abstract: Insomnia in Japanese adolescents is common and associated with multiple factors. The results of this study suggest the need for comprehensive program to prevent insomnia in Japanese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 32 publications
6
92
3
2
Order By: Relevance
“…Reciprocal relations among anxiety, distress, strain, depression and sleep disturbances have been suggested earlier [4,6,30,56]. These psychological symptoms are closely linked to obesity, smoking and physical inactivity [14,17,22,35,43,51,53], which have been suggested as risk factors for neck, shoulder and low back pains in adolescence [5,25,31,32,42]. Our findings that insufficient quantity or quality of sleep increases the risk of neck and low back pains independently of depressive mood, physical activity, sedentary behavior, smoking, BMI and parents' socioeconomic status may indicate that it has a mediating effect, explaining the relationship between social pressures, psychological symptoms and musculoskeletal pains.…”
Section: Discussionmentioning
confidence: 65%
“…Reciprocal relations among anxiety, distress, strain, depression and sleep disturbances have been suggested earlier [4,6,30,56]. These psychological symptoms are closely linked to obesity, smoking and physical inactivity [14,17,22,35,43,51,53], which have been suggested as risk factors for neck, shoulder and low back pains in adolescence [5,25,31,32,42]. Our findings that insufficient quantity or quality of sleep increases the risk of neck and low back pains independently of depressive mood, physical activity, sedentary behavior, smoking, BMI and parents' socioeconomic status may indicate that it has a mediating effect, explaining the relationship between social pressures, psychological symptoms and musculoskeletal pains.…”
Section: Discussionmentioning
confidence: 65%
“…15 It is thus likely that skipping breakfast results in weight gain through increased food intake later in the day when the Breakfast Consumption Association of breakfast skipping with obesity C-J Huang et al body is less likely to expend the energy consumed and consequently increasing energy storage. Skipping breakfast has been found to be associated with undesirable health outcomes such as insomnia, 26 increased blood pressure 27 and cluster with health-compromising behaviors such as smoking, alcohol and lack of exercise. 20 In accordance with previous findings, the results from this study showed that breakfast skipping often coexists with other undesirable health-related habitual behaviors, as we found that breakfast skippers had higher rates of smoking, alcohol consumption, betel quid chewing and lack of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, before concluding that extracurricular activities are indeed detrimental for adolescents' sleep functioning, it is important to note that extracurricular activities may have a protective effect. In a sample of over 100,000 Japanese adolescents, adolescents not participating in an extracurricular activity were at higher risk for experiencing insomnia in comparison to adolescents who did participate in an extracurricular activity (Kaneita et al 2006). Clearly, more research is needed to identify the circumstances or factors that contribute to extracurricular activity use having either a protective or detrimental impact on adolescent sleep.…”
Section: Homework Employment and Extracurricular Activitiesmentioning
confidence: 99%